2018
DOI: 10.3390/polym10040365
|View full text |Cite
|
Sign up to set email alerts
|

Nucleating and Plasticization Effects in Drawn Poly(Lactic Acid) Fiber during Accelerated Weathering Degradation

Abstract: Changes in the polymer properties of poly(lactic acid) (PLA) fibers during drawing and degradation processes were analyzed using solid-state NMR, with the goal of elucidating morphological changes that influence fiber tensile properties. Combination of X-ray diffraction (XRD) and differential scanning calorimeter (DSC) indicated that the drawn PLA fibers consisted of different proportions of α crystalline and amorphous forms. 13C CP-MAS NMR spectra showed amorphous-like broad singlet signals, of which the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…At the same time, the T 1 H values of trace amounts of the PBS unit slightly decreased (1.0 s) in PHA5533L. These T 1 H reductions were caused by the enhancement of the T 1 H relaxation due to the heterogeneity that arose from the amorphous moiety, as we have previously described for PLA copolymer fibers [ 24 ].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…At the same time, the T 1 H values of trace amounts of the PBS unit slightly decreased (1.0 s) in PHA5533L. These T 1 H reductions were caused by the enhancement of the T 1 H relaxation due to the heterogeneity that arose from the amorphous moiety, as we have previously described for PLA copolymer fibers [ 24 ].…”
Section: Resultssupporting
confidence: 67%
“…At the same time, the amorphous peak of PHA clearly increased. The copolymerization of PHA with PLA [PHA5533L (4)] increased further the amorphous peak of PHA; only a small peak of PLA was observed at 2θ = 16.4° (100) [ 24 ]. In both cases of PHA4422P and PHA5533L, characteristic XRD peaks from P4HB could not be assigned.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the occurrence of three components of relaxation times for the PLLA/30 W sample proved poor compatibility between PLLA and the filler. The addition of non-modified wood accelerates crystallization of the PLLA chains when compared to neat PLLA as confirmed by longer relaxation times and lower activation energies [ 88 ]. The NMR results confirmed that using γ-aminopropyltriethoxysilane (APE) as a surface modifier improves interfacial adhesion between wood filler and PLLA.…”
Section: Resultsmentioning
confidence: 99%
“…1 PLA has a lower environmental impact than conventional polymers, besides biocompatibility, biodegradability, and easy processability. 2,3 The high cost of PLA ($2.5-3.2 USD per kg) compared to conventional polymers such as polyethylene and polypropylene ($1.30-1.70 USD per kg) and its low thermomechanical stability 3 make it necessary the development of strategies to overcome these disadvantages. In this sense, natural fibers have been used as reinforcers and fillers to mitigate the PLA limitations.…”
Section: Introductionmentioning
confidence: 99%